Hedging of options under mean-square criterion and semi-Markov volatility - Svishchuk, A.V. (Український математичний журнал, 1995)
We consider a problem of hedging of the European call option for a model in which the appreciation rate and volatility are functions of a semi-Markov process. In such a model, the market is incomplete.